The production and distribution of knowledge in the United States - Machlup, Fritz (Princeton University press, 1962)
The Production and Distribution of Knowledge in the United States marked the beginning of the study of our postindustrial information society. Austrian-born economist Fritz Machlup had focused his research on the patent system, but he came to realize that patents were simply one part of a much bigger "knowledge economy." He then expanded the scope of his work to evaluate everything from stationery and typewriters to advertising to presidential addresses--anything that involved the activity of telling anyone anything. The Production and Distribution of Knowledge in the United States then revealed the new and startling shape of the U.S. economy.